2016
DOI: 10.3390/molecules21040532
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subnanometric Ag Species, Their Interaction with Supports and Role in Catalytic CO Oxidation

Abstract: Abstract:The nature and size of the real active species of nanoparticulated metal supported catalysts is still an unresolved question. The technique of choice to measure particle sizes at the nanoscale, HRTEM, has a practical limit of 1 nm. This work is aimed to identify the catalytic role of subnanometer species and methods to detect and characterize them. In this frame, we investigated the sensitivity to redox pretreatments of Ag/Fe/TiO 2 , Ag/Mg/TiO 2 and Ag/Ce/TiO 2 catalysts in CO oxidation. The joint app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The observed effects can be explained as follows: in as-prepared samples, a significant part of both metals was in the ionic state, that is, Ag + , Au 3+ and Au + [39,40,63]. According to the previously reported results, single-charged ions are active sites of low-temperature oxidation of CO and alcohols, while Au 3+ was inactive in the studied processes [22,39,49,50].…”
Section: Comparison Of Catalytic and Physicochemical Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The observed effects can be explained as follows: in as-prepared samples, a significant part of both metals was in the ionic state, that is, Ag + , Au 3+ and Au + [39,40,63]. According to the previously reported results, single-charged ions are active sites of low-temperature oxidation of CO and alcohols, while Au 3+ was inactive in the studied processes [22,39,49,50].…”
Section: Comparison Of Catalytic and Physicochemical Resultsmentioning
confidence: 71%
“…This is due to the well-reported fact that, in some cases, only gold nanoparticles with sizes below 5 nm showed catalytic activity; the larger particles were simply "spectators" of the process [72][73][74][75][76]. Our previous studies have shown that the active particles are smaller than 2 nm, some of which were undetectable by TEM and XRD methods [63,73]. In addition, in bimetallic samples, it is impossible to discriminate TEM images of Au and Ag clusters.…”
Section: Comparison Of Catalytic and Physicochemical Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The role of sub-nanometric Ag species (on Fe, Mg and Ce modified TiO 2 materials) on catalytic CO oxidation is studied by several techniques in [1]. The observed phenomena cannot be explained only considering the 1-13 nm Ag particle size distributions measured by HRTEM; the existence of Ag species with size < 1 nm, non-visible in HRTEM, and their interaction with the supports, needs also to be taken into account.…”
mentioning
confidence: 99%